2016
DOI: 10.17352/ijpsdr.000007
|View full text |Cite
|
Sign up to set email alerts
|

Edaravone Protects against Vascular Oxidative Damage Induced by AAPH in Chick Embryo

Abstract: Background: Edaravone (Eda) is a free-radical scavenger which is used in treating stroke, cerebral hemorrhage and some other diseases in clinic. However, it's antioxygenation during development is still unknown.Method: An oxidative damage model was established in chick embryo by using a generator of free radicals, 2,2'-azobis[2-methylpropionamidine] dihydrochloride (AAPH). The mortality rate and embryo's weight were measured to detect whether retarded growth happened. In order to observe the blood vessels, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In the present study, decreased cell viability under LPS and AAPH challenge in cPBMCs was remarkably ameliorated by HFAC, with 50 mg/mL had the most effective improvement in average. LPS administration has been applied to set as an optimal model for study inflammation in cells [5]; while AAPH is an azo compound widely used to study the antioxidant effect of certain material since it tends to stimulate oxidative damage in cells [17]. In other words, these suggested that the FAC has potentiality to equip cells with proper defense and tolerance ability toward adverse condition.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, decreased cell viability under LPS and AAPH challenge in cPBMCs was remarkably ameliorated by HFAC, with 50 mg/mL had the most effective improvement in average. LPS administration has been applied to set as an optimal model for study inflammation in cells [5]; while AAPH is an azo compound widely used to study the antioxidant effect of certain material since it tends to stimulate oxidative damage in cells [17]. In other words, these suggested that the FAC has potentiality to equip cells with proper defense and tolerance ability toward adverse condition.…”
Section: Discussionmentioning
confidence: 99%